Structure evolution of lignite char in step pyrolysis and its combustion reactivity. (1st May 2022) - Qi, Jianan; Fan, Chuigang; Wu, Hao; Li, Songgeng
Highlights: Step pyrolysis favors char production, attributed to cross-linking reactions. Step pyrolysis char has lower combustion reactivity relevant to direct pyrolysis. An index was proposed to assess the extent of cross-linking reactions in pyrolysis. Step pyrolysis inhibits N and S releases by forming more stable functionalities. Abstract: Step pyrolysis was conducted in a laboratory-scale fixed bed reactor for char preparation. Characterization techniques such as volume solvent swelling, thermal gravimetric analysis (TGA), X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) were applied to reveal char structure evolution during step pyrolysis. Combustion reactivities of the prepared chars were examined at a thermal gravimetric analyzer. Newly formed bond structures in char such as Cal -Cal and Car -Cal /O have been identified at the 1st stage of step pyrolysis, which evidences the occurrence of cross-linking reactions. As a result, step pyrolysis has higher char yield than direct pyrolysis. The char yield from step pyrolysis increases as the 1st stage pyrolysis temperature increases and reaches a maximum at 773 K. An index was put forward to assess the extent of cross-linking reactions during pyrolysis, which is well correlated with char production. The char from step pyrolysis has relatively high graphitization degree than from direct pyrolysis, and thus has lower combustion reactivity. Step pyrolysis can suppress sulfur and nitrogen release in comparison with direct pyrolysis owing to the formation of more stable sulfur and nitrogen species in char. The difference in nitrogen release varies within 8 percentage points and for sulfur release, it is within 5 percentage points under the examined experimental conditions.